Collective de se thoughts and centered worlds - Liao, Shen-yi (2014)
Two lines of investigation into the nature of mental content have proceeded in parallel until now. The first looks at thoughts that are attributable to collectives, such as bands’ beliefs and teams’ desires. So far, philosophers who have written on collective belief, collective intentionality, etc. have primarily focused on third-personal attributions of thoughts to collectives. The second looks at de se, or selflocating, thoughts, such as beliefs and desires that are essentially about oneself. So far, philosophers who have written on the de se have primarily focused on de se thoughts of individuals. This paper looks at where these two lines of investigations intersect: collective de se thoughts, such as bands’ and teams’ beliefs and desires that are essentially about themselves. There is a surprising problem at this intersection: the most prominent framework for modeling de se thoughts, the framework of centered worlds, cannot model a special class of collective de se thoughts. A brief survey of this problem’s solution space shows that collective de se thoughts pose a new challenge for modeling mental content.